Assessment of Status of Different Nucleated Cell Populations of Cord and Donor Blood Depending on Their Cryopreservation Method - Babiychuk, L. A.; Mikhaylova, O. A.; Zubov, P. M.; Ryazantsev, V. V. (Problems of Cryobiology and Cryomedicine, 2011)
Quantity and viability of nucleated cell (NC) populations of cord and donor blood was assessed after implementation of various cryopreservation method. It has been shown that isolation of cells by polyglukin and their following freeze-thawing under 5% DMSO protection as well as isolation of NCs by two-step centrifugation with following freeze-thawing under 10% PEO-1500 protection allows the preservation of a quantity and viability of cells at quite a high level. Basic reduction of both quantity and viability of NCs independently on the cryopreservation methods used occurs on account of the population of granulocytes, lymphocytes and monocytes occured to be more resistant to damaging cryopreservation factors. Mononuclear cells of cord blood were shown to be more resistant to damaging cryopreservation factors unlike mature cells of adult donor blood that was manifested in significant differences of the indices of cell viability virtually in all cases prior to and after their cryopreservation.